STRATEGIC FEMININITY: ANALYSING WOMEN’S LANGUAGE FEATURES IN OPRAH WINFREY’S INTERVIEWS THROUGH LAKOFF’S FRAMEWORK - Hj. Ahmad, Mahadirin; Djamereng, Jumharia (Universitas Islam Negeri Sunan Gunung Djati, 2025)
The study describes how women use language by using linguistic features in televised interviews featuring prominent female figures, focusing on Oprah Winfrey and her guests, Brené Brown and Esther Perel, which become the characteristics of women's language. It intends to analyse the relevance using of Lakoff’s theory and the strategy of language features produced by women's language. The study was designed using a descriptive qualitative method to describe the women's language features performed by Oprah Winfrey and her guests, Brené Brown and Esther Perel. The instrument was the researchers themselves who played an important role in collecting and analyzing the data. The data were taken from three unscripted interviews that analyzed the use and function of language features like hedges, tag questions, super polite forms, avoidance of strong assertions, empty adjectives, and emphatic stress. Thus, the data were analyzed by using frameworks from Lakoff, Tannen, Holmes, Coates, and Cameron by coding and interpreting them based on pragmatic functions and their relation. The study reveals that these linguistic features do not indicate weakness or deference, but are used as a strategy to communicate, especially in showing empathy, managing authority, and constructing relational identity. The study also shows the absence of selective features such as hypercorrect grammar and precise color terms which indicates adaptation of conversational norms in media discourse. The result supports the understanding of femininity both in performative and rhetorical contexts in which gendered speech is used to reflect identity and as a sensitive practice in a context. It also contributes to the study of language and gender that bridge the classic sociolinguistics theories and contempered discourse in emotionally expressive media